Re-Examining Exit Exams: New Findings from the Education Longitudinal Study of 2002 - Shuster, Catherine (Education Policy Analysis Archives, 2012)
Using the nationally representative, cohort-based data of the Education Longitudinal Study of 2002 (ELS:02), this study employs multiple regression to examine the effects of exit exams on student achievement and school completion. This study finds that exit exams as a whole do not have substantial effects on student achievement in mathematics, twelfth grade GPA, or school completion. Standards-based exams are a positive predictor of dropping out of school but lose their predictive power once GED recipients are coded as completing school. Exit exams do not affect GED seeking and acquisition. When exit exams are disaggregated by type and students are sorted by ninth grade GPA quartiles, end-of-course exams have some negative effects on mathematics test score gains. Students in the bottom two quartiles see reduced test score gains of 28% and 29% of a grade level equivalency (GLE). These effects disappear when students in North Carolina are coded as taking a different type of exam. Standards-based exams had a small positive effect, about 37% of a GLE, on the top quartile of students. Overall, the findings showed no results for school completion and mixed results for test score gains. The article concludes that policymakers looking to boost high school achievement would be better served by working to boost student accomplishments before high school.<!–[if gte mso 9]> Normal.dotm 0 0 1 214 1224 cmc 10 2 1503 12.0 <![endif]–><!–[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]–><!–[if gte mso 9]> <![endif]–><!–EndFragment–>